16th International IEEE Conference on Intelligent Transportation Systems (ITSC 2013) 2013
DOI: 10.1109/itsc.2013.6728523
|View full text |Cite
|
Sign up to set email alerts
|

The influence of time-criticality on Situation Awareness when retrieving human control after automated driving

Abstract: Abstract² When applying automated driving as a means for congestion assistance, developers are challenged how to accommodate the transitions between automated and manually driving, especially because these transitions might occur regularly and suddenly. During automated driving, the ability to take over control is also aggravated due to the driver being placed out of the control-loop. To assess then the ability to retrieve human control, we tested within a driver simulator experiment the influence of criticali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…A number of studies which assessed driver behavior after transition from highly automated driving, found that the shorter time budget decreased the take-over quality, including percent of accidents and maximum longitudinal/lateral acceleration [32,33]. They also found that the higher complexity of the traffic increased the take-over time due to longer situation awareness regaining.…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies which assessed driver behavior after transition from highly automated driving, found that the shorter time budget decreased the take-over quality, including percent of accidents and maximum longitudinal/lateral acceleration [32,33]. They also found that the higher complexity of the traffic increased the take-over time due to longer situation awareness regaining.…”
Section: Resultsmentioning
confidence: 99%
“…The same counts for raised levels of SA. That means if an interface helps to raise SA so does the chance for effective accident avoidance (Gold et al, 2013;Van den Beukel & Van der Voort, 2013). Results from an experiment of the author to test driver's ability to retrieve human control during time-critical take-over scenarios showed that the ability to retrieve control is positively influences if drivers gain increased levels of SA (Van den Beukel & Van der Voort, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In an earlier experiment that measured SA in simulated control-retrieving tasks, the authors found differences between SART and SAGAT approaches (Van den Beukel & Van der Voort, 2013) in that the longer period before situation retrieval with the SAGAT approach had a counter-productive influence on SA accuracy when compared to using the SART. Studies by other authors also raise questions regarding the reliability and validity of SAGAT and SART measurement methods (Endsley et al, 1998;Salmon et al, 2006).…”
Section: B "Cut In"mentioning
confidence: 99%
See 2 more Smart Citations